Yamove! A movement synchrony game that choreographs social interaction - Isbister, Katherine; Segura, Elena; Kirkpatrick, Suzanne; Chen, Xiaofeng; Salahuddin, Syed; Cao, Gang; Tang, Raybit (Human Technology, 2016)
This paper presents a design case study of Yamove!, a well-received dance battle game. The primary aim for the project was to design a mobile-based play experience that enhanced in-person social interaction and connection. The game emphasized the pleasures of mutual, improvised amateur movement choreography at the center of the experience, achieved through a core mechanic of synchronized movement. The project team engaged techniques from the independent (“indie”) game development community that proved valuable in tempering the constraints to which technologically driven design can sometimes fall prey. Contributions of this work include (a) presentation and discussion of a polished digital game that embodies design knowledge about engaging players in mutual physical improvisation that is socially supported by technology, and (b) a case study of a design process influenced by indie game development that may help others interested in creating technologies that choreograph pleasurable intentional human movement in social contexts.